(untitled) (Latakia University Journal -Engineering Sciences Series, 2016)
تناول البحث حساب مردود اللاقط الشمسي ذو الأنابيب المفرغة من نوع "النور" , طول الأنبوب 1500mm, قطره الخارجي 58mm , قطره الداخلي 47mm , سمك الزجاج 1,6mm , مادة الطلاء AL/AL-N , مع خزان حراري بعازل من الصوف الزجاجي سماكة 30mm وله 10 أنابيب المتوفر في الأسواق المحلية , بهدف تحديد الكفاءه الفعلية في شروط مدينة اللاذقية , وتحديد كمية الماء الساخن التي يؤمنها يومياً في كل فصل من فصول السنة , تم وضع اللاقط على قاعدة متحركة يمكن تغيير اتجاهها وتغيير زاوية ميل أنابيب اللاقط لتتبع حركة الشمس , واستخدم جهاز قياس شدة الإشعاع الشمسي ماركة GENERAL DBTU1300 لمعرفة شدة الإشعاع الشمسي الوسطية خلال كل ساعة , وتم حساب ثوابت مردود اللاقط على اعتبار أن الإشعاع الشمسي عمودي على اللاقط , ورسم العلاقة بين المردود والفرق الحراري عند قيم مختلفة لشدة الإشعاع الشمسي , ثم تم أخذ زوايا ميول مختلفة طولية وعرضية من أجل حساب معاملات الميلان الطولية والعرضية له, ورسم علاقة معاملات الميل الطولية والعرضية مع زاوية ميل الشعاع الشمسي, وبالاعتماد على شروط مدينة اللاذقية, ومن الأرصاد الجوية تم تحديد مردود اللاقط الوسطي في كل فصل من فصول السنة , وتحديد كمية الماء الساخن بدرجة حرارة 60 مئوية التي يعطيها يوميا . This study deals with calculation the efficiency of the solar heater with a solar evacuated glass tubes of the type "ALNOR" Tube length 1500mm outer diameter 58mm inner diameter of 47mm thickness glass 1,6mm coating material AL / AL-N tank with thermal insulation of glass wool 30mm thickness with ten tubes available in local markets, in order to determine the efficiency of the actual conditions of the city of Lattakia, and determine the amount of hot water that secures it a day in each season of the year, where I put the solar heater on the base Animations can change direction and change the angle of inclination pipe detector to track the movement of the sun and use the device to measure the intensity of solar radiation by Solar Power Meter brand GENERAL DBTU1300 to see the intensity of solar radiation moderation during each hour, that solar radiation is perpendicular to the detector, and draw a relationship between the efficiency and the difference of thermal at different values ​​of the intensity of solar radiation and then was taken corners Preference different longitudinal and transverse to calculate coefficients inclination longitudinal and latitudinal and draw a relationship slope coefficients longitudinal and lateral with the tilt angle of solar radiation, and depending on the conditions city ​​of Lattakia, and meteorology have been identified in the average return on the detector each season of the year and determine the amount of hot water at 60 Celsius dgrees that gives per day.